Facile preparation of magnetic porous biochars from tea waste for the removal of tetracycline from aqueous solutions: Effect of pyrolysis temperature. (March 2022) - Li, Bin; Zhang, Yin; Xu, Jin; Fan, Shisuo; Xu, Huacheng
Abstract: Pyrolysis process significantly influences the physicochemical properties and potential application of magnetic porous biochars (MPBCs). However, the effects of pyrolysis temperature on the properties of MPBCs as well as substantial adsorption are still unclear. This study reported a facile method to obtain the MPBC from tea waste via pyrolysis of a mixture of hydrochar, KHCO3, and FeCl3 ·6H2 O under different temperatures (500–800 °C), and explored further the adsorption toward tetracycline (TC). Results showed pyrolysis temperature obviously influenced the physicochemical properties of MPBCs, and MPBC pyrolyzed at 700 °C (MPBC-700) has a highest specific surface area (1066 m 2  g −1 ) and pore volume (2.693 cm 3  g −1 ). However, the adsorption potential increased consistently from 59.35 mg g −1 for MPBC-500 to 333.22 mg g −1 for MPBC-800, suggesting that the surface area and pore volume were not the only factors determining TC adsorption. Further analysis showed that the pore-filling, π-π interaction, complexation, and hydrogen bonding contributed together to TC adsorption. Moreover, all MPBCs possessed a high saturation magnetization, indicating the easy separation by an external magnet. Therefore, MPBCs (especially at 700 °C) can act as the excellent adsorbents for contaminant removal due to their high separation, adsorption, and reuse performance. Graphical abstract: Image 1 Highlights: MPBCs pyrolyzed at different temperatures with TC removal were studied. Pyrolysis temperature influenced highly the physicochemical properties of MPBCs. Higher pyrolysis temperature benefited the TC adsorption onto MPBCs. The maximum TC adsorption capacity was 333.22 mg g −1 for MPBC-800. Pore-filling, π-π interaction, and complexation were the main mechanisms for TC adsorption.